Developing an Interactive E-Book for Teaching World War I and II: A Design-Based Research in an Indonesian Senior High School - Wildan Subekti; Atno Atno (Indonesian Journal of History Education, 2025)
This design-based research addresses the scarcity of contextual teaching materials for advanced history classes in Indonesia by developing an interactive e-book on World War I and II. Using the ADDIE model, the study involved needs analysis, design, development, implementation, and evaluation phases at a public high school in Purwokerto. The e-book integrates multimedia, augmented reality, and interactive assessments aligned with the national Independent Curriculum. Validation by subject matter, media, and practitioner experts yielded scores of 100%, 94%, and 98.5%, respectively. Teacher and student responses were highly positive, with satisfaction rates of 100% and 85.65%. Findings indicate that the e-book is a feasible and engaging supplementary resource that supports historical literacy and digital pedagogy in Indonesian classrooms. The study highlights the potential of locally developed digital media to bridge resource gaps and foster critical historical awareness in post-colonial educational contexts.